A methodology and a database for forecasting anthropogenic atmospheric emissions in Europe - Samaras, Zissis; Holtmann, T.; Rentz, O.; Zierock, Karl Heinz; Zachariadis, Theodoros (My University, 1999)
A methodology developed for technology-oriented emission forecasts is outlined. It comprises predictions of activity rates for all anthropogenic emission sources as well as assessment of the ageing and technology substitution processes of individual installations or equipment, and combines these with submodules that calculate emissions for each subsector on an annual basis. All data necessary to apply this methodology for the pre-1995 12 European Union member states (i.e. Belgium, Denmark, Germany, Spain, France, Greece, Ireland, Italy, Luxembourg, the Netherlands, Portugal and the United Kingdom) have been collected and are included in databanks of a computer model called CASPER. The results of a run performed with the model according to a realistic base case scenario are presented and discussed.
Keywords: Computer model; Emissions; Projection; Technology substitution